Queue Management and Application in Supermarket - MOHAMAD SAFURI, AMIRUL AZFAR; KAMARDAN, MUHAMAD GHAZALI (Enhanced Knowledge in Sciences and Technology, 2022)
This study focuses on a queuing simulation of a supermarket using Arena Simulation Software. The goal of this research is to learn more about Arena Simulation Software and to examine the supermarket’s queuing problem. Throughout this study, three factors were examined: Average Waiting Time of Customer (Wq), Average Number of Waiting Customers (Lq), and Instantaneous Utilization. The simulation model result shows that the (Wq) is 13.84 minutes, (Lq) is 3 customers and the Instantaneous Utilization is 89%. These conditions are considered to be well utilized. We also try to simulation the outcome if the supermarket adds another server. From the analysis, it was found that (Wq) is 8.74 minutes, (Lq) approximately is 1 customer, and Instantaneous Utilization is 45%. Although (Wq) and (Lq) show well improved results, however we found that the is below the utilization capacity. Thus, we suggest the supermarket do not need to add another cashier and use just one cashier to serve customers.